UNDERSTANDING GREEN CONSUMERS: A BIBLIOMETRIC ANALYSIS OF ENVIRONMENTAL ATTITUDE AND GREEN PURCHASE BEHAVIOR - Prawita Megatama; Retno Widowati; Siti Dyah Handayani (Asosiasi Dosen Muda Indonesia, 2024)
This study conducts a bibliometric analysis of research on green purchase behavior from 2017 to 2023, utilizing data from the Scopus database. A total of 355 articles were selected and analyzed to identify trends in consumer behavior towards environmentally friendly purchases. The findings reveal a significant increase in publications, with a peak anticipated in 2023, indicating a growing interest in the intersection of consumer behavior and environmental sustainability. Key contributors to the field include prolific authors and journals, with China emerging as the leading country in terms of published research. The analysis highlights the critical role of positive environmental attitudes in fostering pro-environmental behaviors, such as the purchase of green products. Additionally, the study identifies factors influencing this relationship, including perceived consumer effectiveness and the need for effective educational strategies. The results underscore the importance of understanding consumer motivations and behaviors to inform marketing strategies and enhance sustainability initiatives. This research contributes to the literature by providing a comprehensive overview of the current state of green purchase behavior research and suggesting avenues for future inquiry.